Pengharapan Akan Kedatang Yesus Kembali Di Dunia Ini - Setulus Hati Laia; Aprianus Lendrik Moimau (Journal New Light, 2024)
The hope in the return of Jesus Christ is a central concept in Christian theology that has been a source of comfort, strength, and motivation for Christians for centuries. This concept refers to the belief that Jesus Christ, as the son of God, will return to this world to complete his plan of salvation and begin a new era marked by justice, peace, and eternity. This abstract provides a brief overview of the hope in Jesus' return, including its theological foundations in the Bible, various theological interpretations, and its practical implications for personal life and the Christian community. Through understanding this hope, Christians are given a call to live in faithfulness, obedience, and constant preparation, and to share the message of salvation with my world. The hope of the return of Jesus Christ is not only the focus of worship and spiritual reflection, but also the driving force for just social action and comprehensive love in a world filled with suffering and need.